Earmarking Donations to Charity: Cross-cultural Evidence on Its Appeal to Donors Across 25 Countries - Fuchs, Christoph; de Jong, Martijn G.; Schreier, Martin (Management Science, 2020)
Charity organizations differ in their practice of offering donors the option to earmark their contribution: allowing donors to select the project in which their money should be invested. This paper presents two studies that provide the first empirical evidence on the appeal of such earmarking. The empirical basis of Study 1 is a unique data set consisting of 7,383 potential donors from 25 countries who participated in a randomized survey experiment. First, we find that the willingness to donate is significantly higher when earmarking is allowed. Second, we find that the effect of earmarking substantially differs in magnitude across countries. Third, we identify two cross-cultural interactions. Specifically, earmarking is less effective in countries that score lower on autonomy relative to embeddedness and in those scoring lower on egalitarianism relative to hierarchy. Fourth, we find that the earmarking effect is driven mainly by the activation of more donors and not by increases in the amounts that donors contribute. Study 2 is a follow-up experiment that replicates the basic earmarking effect, addresses limitations of our cross-cultural study, and sheds some preliminary light on the effect’s underlying process. We find that earmarking options increase potential donors’ perceptions of being able to make specific impact and also that this sense of agency helps us to understand an individual’s increased willingness to donate. This paper was accepted by Eric Anderson, marketing.